The implementation of Sports through Cheerful Gymnastics Video in Improving the Learning Achievement of Students with Dyslexia: Learning with Students without Obstacles - Ambarita, Uly Dame Ria; Sunardi, Sunardi (Angstrom Centre of Education, 2023)
Sports are activities that children really like when they are at school. Cheerful gymnastics is morning gymnastics accompanied by upbeat music, but the movements have been adapted to the songs the children like. This study aims to see the impact of learning achievement from implementing sports activities every morning at an elementary school in Surabaya. Sports activities are conveyed through videos to dyslexic children in a class with children without obstacles. Dyslexia is a child with difficulty in reading. Implementation is carried out every day for 6 months, observing the learning process and collecting learning outcomes in each subject for 6 months. The research subjects were 4D elementary school students at a private school in Surabaya. This research was conducted using a qualitative descriptive method by describing in detail the condition of the students, the environment, and the conditions during learning. Achievement is seen by collecting valuable data from each lesson and comparing it to see the impact obtained after participating in sports activities every day for 6 months. The results are very significant. The number of students who get remedial during tests/exams is far less than the other 4th graders.